Tourism Students’ Perception of Using TikTok in Learning English Vocabulary Mastery - Ni Nyoman Suriasmini (Fakultas Dharma Duta UHN IGB Sugriwa Denpasar, 2024)
This research aimed to analyze the students’ perception toward TikTok in learning English vocabulary. The objective of the research is (1) to investigate students’ perception of using TikTok in learning English vocabulary, (2) to figure out the implications of TikTok in learning English vocabulary mastery. This research was conducted online for English tourism students of university in Bali. The data was collected from the questionnaire through google form and was shared online. the result of the study showed that the quantitative data revealed that participants had positive perceptions toward TikTok in learning English vocabulary. For instance, most of them agree that TikTok is fruitful tool for learning vocabulary, majority of participants agree that they found new words on TikTok. These finding suggest that students can use TikTok for learning vocabulary and increasing their language skills to be better.